Study of the influence of the contact model on the dynamic response of a biomechanical multibody knee model - Machado, Margarida
This work presents a study of the influence of the contact model on the dynamic response of the human knee joint. For this purpose a multibody knee model composed by two rigid bodies, femur and tibia, and four nonlinear springs that represent the main knee ligaments, was used. Computational simulations were performed to investigate and compare three modeling parameters, namely contact law, contact geometry and material properties. The contact laws considered here are the Hertz, the Hunt-Crossley and the Lankarani-Nikravesh models. This study showed that Hertz law is less appropriate than the other two models to describe the dynamic response of cartilage, because it does not account for its viscoelastic nature. Since knee can exhibit conformal and non-conformal contact scenarios, three distinct geometrical models for femur-tibia were considered: convex sphere-plane, convex-convex spheres and convex-concave spheres. The highest level of contact forces was obtained for the conformal scenario. Concerning to the influence of the properties of the contacting materials, the dynamic response of a healthy knee was compared to three pathologic and two artificial knees. The results demonstrated that the cartilage reduces the peak force experienced by the models without cartilage and extend the impact loading period over a longer time.